Bismuth-induced synthesis of Au–X (X = Pt, Pd) nanoalloys for electrocatalytic reactions. Issue 3 (16th December 2020) - Wang, Nan; Zhao, Wei; Zhang, Miaolei; Cao, Pengfei; Sun, Shengjun; Ma, Houyi; Lin, Meng
Abstract : The synthesis of Au–X (X = Pt, Pd) nanoalloys based on Bi as an intermediate using the galvanic replacement reaction method for electrocatalytic reaction. Abstract : Bismuth was introduced as an intermediate to produce Au–X (X = Pt and Pd) bimetallic nanoalloys using the galvanic replacement reaction. The results showed that the Au–X nanoalloys have good activity for electrocatalytic reactions in alkaline media. This strategy can provide an option for the formation of multimetal nanoalloys with similar electrochemical potentials and compositions.